REGULATION OF INITIATION OF DNA SYNTHESIS IN CHINESE HAMSTER CELLS : II. Induction of DNA Synthesis and Cell Division by Isoleucine and Glutamine in G(1)-Arrested Cells in Suspension Culture - Ley, K. D. (The Rockefeller University Press, 1970)
Suspension cultures of Chinese hamster cells (line CHO), which had stopped dividing and were arrested in G(1) following growth to high cell concentrations in F-10 medium, could be induced to reinitiate DNA synthesis and to divide in synchrony upon addition of the appropriate amounts of isoleucine and glutamine. Both amino acids were required to initiate resumption of cell-cycle traverse. Deficiencies in other amino acids contained in F-10 medium did not result in accumulation of cells in G(1), indicating a specific action produced by limiting quantities of isoleucine and glutamine. In the presence of sufficient glutamine, approximately 2 x 10(-6) M isoleucine was required for all cells to initiate DNA synthesis in a population initially containing 1.5 x 10(5) cells/ml. Under similar conditions, about 4 x 10(-6) M isoleucine was required for all G(1)-arrested cells to progress through cell division. In contrast, 1 x 10(-4) M glutamine was necessary for maximum initiation of DNA synthesis in G(1) cells, along with sufficient isoleucine. A technique for rapid production of G(1)-arrested cells is described in which cells from an exponentially growing population placed in F-10 medium deficient in both isoleucine and glutamine or isoleucine alone accumulated in G(1) after 30 hr.